Study Of Some Of The Physical And Skills Qualities Of Football Goalkeepers For The Teams Of Al-djelfa State Active In The Second Regional Section Field Study For 15-19 Year Olds - Karboua, Kamel; Mahour Bacha, Mourad; Ferahtia , Sabira (sports creativity, 2025)
The study aims to explore the important physical characteristics of this category: (strength, sustainability, speed, compatibility, flexibility), by establishing a series of physical and field tests for the teams of Al-Jelfa state for the age group 15-19 years, as well as the detection of the skilled aspects of the same category through the establishment of skill tests agreed by the trainers and doctors, and the sample of our research reached 20 goalkeepers selected deliberately from the state teams